2015
DOI: 10.1016/j.physletb.2015.08.027
|View full text |Cite
|
Sign up to set email alerts
|

Extremal rotating black holes in the near-horizon limit: Phase space and symmetry algebra

Abstract: We construct the NHEG phase space, the classical phase space of Near-Horizon Extremal Geometries with fixed angular momenta and entropy, and with the largest symmetry algebra. We focus on vacuum solutions to d dimensional Einstein gravity. Each element in the phase space is a geometry with SL(2, R) × U (1) d−3 isometries which has vanishing SL(2, R) and constant U (1) charges. We construct an on-shell vanishing symplectic structure, which leads to an infinite set of symplectic symmetries. In four spacetime dim… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
60
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 32 publications
(64 citation statements)
references
References 35 publications
4
60
0
Order By: Relevance
“…It was shown that the Virasoro algebra of Near Horizon Extreme Kerr consists of symplectic symmetries 1 [25,26] that do not actually require fall-off conditions for the metric; instead one can construct a family of mutually diffeomorphic but physically inequivalent solutions that span a phase space of "boundary gravitons".…”
Section: Jhep04(2018)025mentioning
confidence: 99%
See 4 more Smart Citations
“…It was shown that the Virasoro algebra of Near Horizon Extreme Kerr consists of symplectic symmetries 1 [25,26] that do not actually require fall-off conditions for the metric; instead one can construct a family of mutually diffeomorphic but physically inequivalent solutions that span a phase space of "boundary gravitons".…”
Section: Jhep04(2018)025mentioning
confidence: 99%
“…In this work we study the symplectic symmetry group of the near-horizon region of a large class of extremal black holes in diverse dimensions, specifically the Near-Horizon Extremal Geometries (NHEGs) of [25,26,33]. These are solutions of (n + 4)-dimensional vacuum Einstein equations with SL(2, R)×U(1) n+1 isometry.…”
Section: Jhep04(2018)025mentioning
confidence: 99%
See 3 more Smart Citations